Kemampuan Literasi Sains Siswa Melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) berbasis Culturally Responsive Teaching (CRT) - Safira , Ghina; Agustina, Lina (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: This research is motivated by the low level of science literacy in Indonesia. Science literacy is essential for students as it can foster critical thinking and problem-solving skills. This study aimed to determine the application of Problem-based Learning based on culturally responsive teaching (CRT) to students with science literacy skills. Method: This type of research is pre-experimental, using a science literacy test design. The sample of this study was class VII A, totaling 32 students. The sampling technique used was a simple random sampling technique. The analysis technique used in this research is descriptive statistical analysis. Results: The results of this study indicate that the application of Problem-Based Learning based on Culturally Responsive Teaching (CRT) to science literacy skills is included in the high category seen from the average score of the science literacy test obtained, which is a score of 71,71. Conclusion: The problem-based learning model based on culturally responsive teaching (CRT) involves students, allowing them to quickly identify problems independently or in groups and providing meaningful learning experiences by understanding culture.